Transitional circulation and hemodynamic monitoring in newborn infants - Chakkarapani, AA; Roehr, CC; Hooper, SB; te Pas, AB; Gupta, S (Springer Nature [academic journals on nature.com], 2023)
Transitional circulation is normally transient after birth but can vary markedly between infants. It is actually in a state of transition between fetal (in utero) and neonatal (postnatal) circulation. In the absence of definitive clinical trials, information from applied physiological studies can be used to facilitate clinical decision making in the presence of hemodynamic compromise. This review summarizes the peculiar physiological features of the circulation as it transitions from one phenotype into another in term and preterm infants. The common causes of hemodynamic compromise during transition, intact umbilical cord resuscitation, and advanced hemodynamic monitoring are discussed. Impact: Transitional circulation can vary markedly between infants. There are alterations in preload, contractility, and afterload during the transition of circulation after birth in term and preterm infants. Hemodynamic monitoring tools and technology during neonatal transition and utilization of bedside echocardiography during the neonatal transition are increasingly recognized. Understanding the cardiovascular physiology of transition can help clinicians in making better decisions while managing infants with hemodynamic compromise. The objective assessment of cardio-respiratory transition and understanding of physiology in normal and disease states have the potential of improving short- and long-term health outcomes.